If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 73 + -6x = 30x + 17 Reorder the terms: 73 + -6x = 17 + 30x Solving 73 + -6x = 17 + 30x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30x' to each side of the equation. 73 + -6x + -30x = 17 + 30x + -30x Combine like terms: -6x + -30x = -36x 73 + -36x = 17 + 30x + -30x Combine like terms: 30x + -30x = 0 73 + -36x = 17 + 0 73 + -36x = 17 Add '-73' to each side of the equation. 73 + -73 + -36x = 17 + -73 Combine like terms: 73 + -73 = 0 0 + -36x = 17 + -73 -36x = 17 + -73 Combine like terms: 17 + -73 = -56 -36x = -56 Divide each side by '-36'. x = 1.555555556 Simplifying x = 1.555555556
| X-.28x=463.32 | | 2-4y=1-5y | | 3x+(2x+4)=5(x+1)+3 | | 5x+6=-69 | | -4[x-2(2x-3)]+1=x-3 | | x-(-50)=55 | | -10-8p+15+9p=2 | | 11x^2-8=432 | | 6+0.60x=13.20 | | -9+3b=12 | | 8-5q=21-2q | | 6X(2x-5)=0 | | x-(-54)=-11 | | 2y^2+10y-48= | | 9x+9+4x=39 | | Y=x^2+9x+19 | | x-62=-20 | | 7-5x=x-12 | | 2x^2-48x=0 | | (-1)x=-(-10) | | 4(6y-12)-2y=-4 | | -x+92=2x-3x | | x^2-4s+4=0 | | 16+x=-73 | | X+17-3X=11 | | 227-5x=81+19 | | 3x+38=11x-26 | | (-5)x=-(-10) | | 0.4-1.2=0.3+0.6 | | q+16=-3 | | x-(-37)=55 | | 3ln(2)-2ln(3)=0 |